PENGARUH RASIO SUSU SAPI DENGAN SUSU ALMOND DAN KONSENTRASI SARI BUNGA TELANG (Clitoria ternatea L.) TERHADAP KARAKTERISTIK ES KRIM [THE EFFECT OF THE RATIO OF COW’S MILK TO ALMOND MILK AND THE CONCENTRATION OF BLUE PEA FLOWER (Clitoria ternatea L.) EXTRACT ON THE CHARACTERISTICS OF ICE CREAM] - Siregar, Tagor M (Universitas Pelita Harapan, 2022)
Ice cream is a food product that made using milk. Generally, the milk used in making ice cream comes from animals, namely cow’s milk, which contains saturated fatty acid components so that it can cause various degenerative diseases. Almond milk comes from plants so it can be used to reduce the amount of cow's milk and produce low-fat ice cream. The blue pea flower has long been known for its benefits as a source of antioxidants and natural dye. The purpose of this research is to determine the effect of the ratio of cow's milk to almond milk and the concentration of blue pea flower extract on the characteristics of ice cream. The factors in this research were the ratios of cow’s milk to almond milk (100:0, 75:25, 50:50, 25:75, 0:100) and the concentrations of blue pea flower extract (10, 20, 30%). The obtained ice cream was analyzed based on physicochemical and sensory properties. The best ice cream was ice cream with a ratio of cow's milk to almond milk of 25:75 and concentration of 10% blue pea flower extract. The results of the sensory analysis showed that the addition of blue pea flower extract could decrease the acceptability of ice cream. The best ice cream was preferred by the panelists and gave the best physical characteristics based on the level of preference (hedonic). The best ice cream has an antioxidant activity (IC50) of 20349 ± 0,06 ppm, overrun of 40,44±2,69%, melting time of 18,10±0,23 minutes, viscosity of 55,13 ± 0,32 cP, ohue of 290,09°, fat content of 1,60 ± 1,16%, and total anthocyanin content of 23,67 ± 1,75 mg/L.Bahasa Indonesia Abstract:Es krim merupakan salah satu produk makanan yang dibuat menggunakan susu. Pada umumnya, susu yang digunakan dalam pembuatan es krim berasal dari sumber hewani yaitu susu sapi yang memiliki kandungan asam lemak jenuh sehingga dapat menyebabkan berbagai penyakit degeneratif. Susu almond yang berasal dari sumber nabati dapat dipilih untuk mengurangi penggunaan susu sapi dan menghasilkan produk es krim rendah lemak. Bunga telang telah lama dikenal manfaatnya sebagai sumber antioksidan dan sebagai pewarna alami. Penelitian ini bertujuan untuk mengetahui pengaruh rasio susu sapi dengan susu almond dan konsentrasi sari bunga telang terhadap karakteristik es krim. Pada penelitian ini yang menjadi faktor penelitian adalah rasio susu sapi: susu almond (100:0, 75:25, 50:50, 25:75, 0:100) dan konsentrasi sari bunga telang (10%, 20%, 30%). Es krim yang dihasilkan dianalisis berdasarkan karakteristik fisikokimia dan sensori. Es krim terbaik adalah es krim dengan rasio susu sapi: susu almond 25:75 dan konsentrasi sari bunga telang 10%. Hasil analisis sensori menunjukkan bahwa penambahan sari bunga telang hingga 30% dapat menurunkan tingkat penerimaan es krim. Es krim terbaik lebih disukai panelis dan menunjukkan karakteristik fisik terbaik berdasarkan tingkat kesukaan (hedonik). Es krim terbaik memiliki aktivitas antioksidan 20349 ± 0,06 ppm, overrun 40,44±2,69%, waktu leleh 18,10±0,23 menit, viskositas 55,13 ± 0,32 cP, ohue 290,09°, kadar lemak 1,60 ± 1,16%, dan kandungan antosianin 23,67 ± 1,75 mg/L.